Tekstualitas Dan Kontekstualisasi Ajaran Islam Dalam Al Quran Dan Hadis - Ridwan Sahrani; Indo Santalia; Tabhan Syamsu Rijal; Abdul Rachman Sahrani (Journal of Innovative and Creativity, 2025)
This article explores two major approaches in understanding Islamic religious texts: the textual (literalist) approach and the contextual (interpretive) approach, and their implications for contemporary Muslim life. The textual approach emphasizes a literal reading of the Qur’an and Hadith, while the contextual approach takes into account historical, social, and maqāṣid al-sharī‘ah considerations. Using a qualitative library research method, this study examines selected verses and hadiths interpreted through both lenses and proposes an integrative (wasatiyyah) approach to address contemporary challenges without compromising Islam’s normative foundations. The findings reveal that synthesizing both approaches provides an understanding that is both authoritative and socially relevant.